Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1080/18811248.2000.9714988
|View full text |Cite
|
Sign up to set email alerts
|

Fusion-Driven Transmutation of Fission Product Cesium in its Elemental Form

Abstract: Assuming fission reaction as a dominant energy source for a long-term perspective, the goal of transmutation of fission products is to cut their increasing accumulation and to keep their inventories at easily manageable level. Opposite to relatively short-lived 137 Cs (T1; 2 =30 yr) whose natural decay converge equilibrium mass to the level of order of 1 t per GW of fission energy, an approach to similar equilibrium inventory for longlived 135 Cs (T1; 2 =2.3x 10 6 yr) requires artificial transmutation that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…8. The neutroninduced transmutation is almost driven by emitting only nu-cleons or a light nucleus such as deuteron, triton, 3 He, and alpha. Particularly, the greatest contribution of (n,xn) reactions prevents it from converting 126 121 Sn, and 113 Sn) with a half-life of less than 1 year.…”
Section: Transmutation Performance 1 Proton Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…8. The neutroninduced transmutation is almost driven by emitting only nu-cleons or a light nucleus such as deuteron, triton, 3 He, and alpha. Particularly, the greatest contribution of (n,xn) reactions prevents it from converting 126 121 Sn, and 113 Sn) with a half-life of less than 1 year.…”
Section: Transmutation Performance 1 Proton Utilizationmentioning
confidence: 99%
“…Almost all the SLSPs decay out during the cooling time. 3 H and 125 Sb are responsible for the magnitude of total equilibrium radioactivity of spallation products. Figure 17(a) shows the time evolution of radioactivity calculated by using Eq.…”
Section: Equilibrium Radioactivity and Toxicitymentioning
confidence: 99%
“…8. The neutroninduced transmutation is almost driven by emitting only nucleons or a light nucleus such as deuteron, triton, 3 He, and alpha. Particularly, the greatest contribution of (n,xn) 113 Sn) with a half-life of less than 1 year.…”
Section: Transmutation Performance 1 Proton Utilizationmentioning
confidence: 99%
“…1) A fusion neutron source of specific quality was proposed there as a candidate for the transmutation of LLFPs. Succeeding research studies [2][3][4][5][6] have been performed on the LLFP transmutation by using highly moderated fusion neutron source in a high-flux fusion-driven blanket. The results showed that LLFPs could be effectively transmuted in the thermal flux blanket of fusion neutron source with the intensity typical for the ITER project.…”
Section: Introductionmentioning
confidence: 99%
“…Second, at fusion neutron energies ( 14MeV for the D-T reaction), transmutation of ssion products is possible through several reactions, such as (n, γ), (n, 2n), (n, 3n), (n, p), (n, d) or (n, α), while for lower energy neutrons, such as ssion neutrons, the only relevant process is (n, γ). Recent reviews of the potential of transmutation of certain ssion products (Cs-137, I-129, Sn-126, Zr-93) in fusion devices are [296,297,298,337,343,344].…”
Section: Nuclear Fusion Devicesmentioning
confidence: 99%